Study on the Mechanical Properties of Stone-Coal Composite under the Influence of Proportioning - Li, Zihao (International Journal of Natural Resources and Environmental Studies, 2025)
With the continuous advancement of backfill mining technology, the continuous mining and gangue backfilling technique has gradually become a key research focus in the field of coal mine backfill mining. By integrating continuous excavation technology with gangue backfilling processes, this approach effectively addresses environmental challenges such as surface subsidence and gangue accumulation. While achieving subsidence reduction and controlled emissions, it also facilitates the recovery of coal reserves trapped under buildings, water bodies, and railways, as well as irregular residual coal deposits, thereby resolving the dilemma of exhausted minable coal resources. However, current research on the synergistic bearing mechanisms between backfill bodies and coal pillars during the continuous mining and backfilling process remains limited. This paper investigates the failure characteristics of the "stone-coal" composite structure and conducts uniaxial compression experiments to analyze the mechanical properties and bearing capacity under varying cement ratios and gangue gradations. The results indicate that the stress-strain curves of the specimens can be divided into four stages: compaction, linear elasticity, plastic failure, and post-peak behavior. Compared to standalone coal samples, the compressive strength of the stone-coal composite is significantly enhanced. Unlike the stress-strain curve of pure coal pillars, no abrupt stress drop occurs in the post-failure stage, and the composite maintains certain residual support strength. This significantly mitigates the risk of sudden coal pillar collapse caused by stress concentration, thereby effectively protecting the coal pillars.